Kana Passambe ‘Pronomina’ pada Teks Cerita Rakyat Makassar - Riyatni Imas Garina (Syntax Idea, 2021)
This research is a qualitative research with an analysis of the functions and roles of kana passambe ‘pronouns’ in the text of Makassar folklore. The data used is written data. The written data is in the form of kana passambe which consists of kana passambe kale, panjojjok, and tampak which appears to be taken from a textbook of Makassar folk tales. Data collection techniques used in written data are documentation techniques, reading techniques and note taking techniques, then the data collected is analyzed descriptively qualitatively. The results of the data analysis show that: first, the function and role of kana passambe kale ‘personal pronouns’ which consist of the first, second, and third (singular and plural) personal pronouns in the Makassar folklore text found two functions, namely the function as object and subject along with three roles, namely the role of sufferer, actor, and receiver. Second, the function and role of kana passambe panjojjok ‘pointer pronoun’ in the Makassar folklore text found three functions, namely the function of the subject attribute, the function of the object attribute, and the function of description along with eight roles, namely the role of actor, experience, participant, tool, place, time, recipients, and sufferers. Third, the function and role of kana passambe tampak is seen as ‘place pronoun’ in the Makassar folklore text, where only one function is found, namely the function of information along with two roles, namely the role of place and existence.